Pengaruh Leverage dan Likuiditas Terhadap Kinerja Perusahaan Pertambangan - Melyana Rizky; Sri Wahyuni Jamal; Rahman Anshari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to analyze the effect of leverage and liquidity on the performance of mining companies listed on the Indonesia Stock Exchange (BEI) in 2015-2023. The sampling technique in this research was purposive sampling technique, so the sample in this research was 13 mining companies listed on the Indonesia Stock Exchange (BEI) in 2015-2023. The data analysis technique used in this research is multiple linear regression. The results of this study indicate that the leverage variable partially has a multiple linear regression value of -0.019 and a significance of 0.065 in the t test, which means that leverage has a negative and insignificant effect on the performance of mining companies and the liquidity variable partially has a multiple linear regression value of 0.017 and a significance of 0.000 in the t test, which means that liquidity has a positive and significant effect on the performance of mining companies.